2005
DOI: 10.1897/04-063r.1
|View full text |Cite
|
Sign up to set email alerts
|

Covert signal disruption: Anti‐ecdysteroidal activity of bisphenol a involves cross talk between signaling pathways

Abstract: Bisphenol A is a key industrial chemical used in the manufacture of polycarbonate plastics and other products. Several recent reports ascribe toxicological properties to this compound that have been attributed to the disruption of endocrine-related processes. In the present study, the toxicity of bisphenol A was definitively characterized in the water flea (Daphnia magna) in an effort to discern whether this compound may elicit endocrine toxicity in an invertebrate species and to establish the mechanism by whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 40 publications
2
21
0
3
Order By: Relevance
“…Several studies have reported effects of environmental chemicals that are consistent with interference with ecdysteroid signaling, though a precise mechanism of action was not established. The chemicals 4-nonylphenol [69], propiconazole [70], and bisphenol A [71], have elicited effects in crustaceans consistent with anti-ecdysteroidal activity. The fungicides propiconazole [72] and fenarimol [73] inhibit cytochromeP450 (CYP) enzymes that are critical to ecdysteroid synthesis.…”
Section: Toxicity Of Chemicals That Mediated Endocrine Disruption On mentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies have reported effects of environmental chemicals that are consistent with interference with ecdysteroid signaling, though a precise mechanism of action was not established. The chemicals 4-nonylphenol [69], propiconazole [70], and bisphenol A [71], have elicited effects in crustaceans consistent with anti-ecdysteroidal activity. The fungicides propiconazole [72] and fenarimol [73] inhibit cytochromeP450 (CYP) enzymes that are critical to ecdysteroid synthesis.…”
Section: Toxicity Of Chemicals That Mediated Endocrine Disruption On mentioning
confidence: 97%
“…The 4-Nonylphenol is an antagonist of the insect ecdysteroidreceptor in vitro [62]. Bisphenol A was proposed to elicit anti-ecdysteroidal activity through a receptor cross-talk mechanism [71,74]. Thus, it is mechanistically plausible that all of these compounds elicit toxicity to crustaceans via perturbations in ecdysteroid signaling.…”
Section: Toxicity Of Chemicals That Mediated Endocrine Disruption On mentioning
confidence: 99%
“…The chemicals 4-nonylphenol (Shurin and Dodson 1997;LeBlanc et al 2000), propiconazole (Kast-Hutcheson et al 2001), and bisphenol A (Mu et al 2005), have elicited effects in crustaceans consistent with anti-ecdysteroidal activity. The fungicides propiconazole (Ronis et al 1998) and fenarimol (Williams et al 2000) inhibit cytochrome P450 (CYP) enzymes that are critical to ecdysteroid synthesis.…”
Section: Aberrant Ecdysteroid Signalingmentioning
confidence: 99%
“…Bisphenol A inhibits reproduction and development rates with an NOEC of 1000 mg l 21 (Brennan et al 2006) and affected intermolt duration at 9000 mg l 21 (Mu et al 2005). In the marine copepods A. tonsa and Tigriopus japonicus, BPA has been shown to inhibit development at 100 and 0.1 mg l…”
mentioning
confidence: 99%
“…In the D. melanogaster BII cell line, BPA was shown to act as an ecdysteroid antagonist, but only at a high exposure concentration of 22.8 mg l 21 (Dinan et al 2001). Studies combining BPA with other chemicals have shown interactive effects, affecting the number of embryo abnormalities and offspring emergence (Mu et al 2005;Wang et al 2005). In summary, for studies in aquatic arthropods, BPA appears to interfere with their hormone systems-possibly by affecting the synthesis of HSPs and/or by interfering with the ecdysone receptor itself-and causes adverse effects at concentrations in the low mg l 21 range.…”
mentioning
confidence: 99%